Community seed banks in Nepal: 2nd National Workshop Proceedings, 3-5 May 2018, Kathmandu - Joshi, B.K.; Shrestha, P.; Gauchan, D.; Vernooy, Ronnie (NAGRC, LI-BIRD and Bioversity International, 2018)
Community seedbanks in Nepal have a long and rich history. In 2018, a national workshop celebrated the achievements and challenges of the community seedbank movement in the country. Farmers, researchers, NGO staff and policymakers discussed key organizational, technical and policy issues. These proceedings present an overview of the state of the art of community seedbanking in Nepal.